Final Selection of Quality Protein Popcorn Hybrids - Parsons, Leandra; Ren, Ying; Yobi, Abou; Angelovici, Ruthie; Rodriguez, Oscar; Holding, David R. (Frontiers in Plant Science, 2021)
Quality Protein Popcorn (QPP) BC2F5 inbred lines were produced through an interpopulation breeding system between Quality Protein dent Maize (QPM) and elite popcorn germplasm. In 2019, five QPP F1 hybrids were selected for further evaluation due to superior agronomics, endosperm protein quality, and popping quality traits. Though these BC2F5 QPP hybrids were phenotypically similar to their popcorn parents, the QPP cultivars conveyed slightly inferior popping characteristics when compared to the original popcorn germplasm. The objective of this study was two-fold. First, BC2F5 inbred lines were crossed to their popcorn parents and BC3F4 inbred lines were produced for hybridization to test the agronomic, protein, and popping trait effects from an additional QPP by popcorn backcross. Second, BC2- and BC3- hybrids were simultaneously evaluated alongside ConAgra Brands® elite cultivars and ranked for potential commercialization in the spring of 2020. These ten QPP hybrids were grown alongside five ConAgra Brands® elite popcorn cultivars in three locations and agronomic, protein quality, and popping quality traits were evaluated. Significant improvements in popcorn quality traits were observed in the QPP BC3 cultivars compared to their BC2 counterparts, and yield averages were significantly lower in BC3 derived QPP hybrids compared to the BC2 population. Protein quality traits were not significantly different between QPP backcrossing populations and significantly superior to ConAgra elite popcorn varieties. Utilizing a previously published ranking system, six QPP hybrids, three from the BC2F5 population and three from the BC3F4 population, were evaluated as candidates for final selection. The successful evaluation and ranking system methodology employed is transferable to other hybrid production and testing programs. Incorporating this analysis with concurrent sensory studies, two QPP hybrids were chosen as premier cultivars for potential commercialization.